Risk assessments of contaminated sediments from the perspective of weight of evidence strategies – a Swedish case study. Issue 5 (11th November 2020) - Bruce, Peter; Sobek, Anna; Ohlsson, Yvonne; Bradshaw, Clare
Abstract: Several countries currently lack common recommendations specific to Ecological Risk Assessment (ERA) of contaminated sediments and stakeholders report inconsistencies between currently used approaches. The objective of this study was to provide an increased understanding of how ERAs of contaminated sediments are conducted in comparison to established guidelines. For this, we use Sweden as a case study and compare seven ERAs with four internationally established strategies. Our results indicate that contaminant concentrations receive a comparatively high weight, despite a lack of appropriate benchmarks; toxicity measurements are uncommon, while routine in established strategies; and the integration and interpretation of results lack transparency. We identify three areas that may help improve the practice of ERAs: a common approach to benchmarks, recommendations for how to assess toxic effects, and a common approach for integrating and interpreting results.